Automating Yapi Kredi Bank archives – a case study - (:unkn) unknown (My University, 2000)
Archivists, records managers, and librarians need to manipulate large amounts of data every day. Many people believe that this requires specially designed, complicated and expensive software. However, depending on your setting, the specifics of what you want to do and how comfortable you feel with computers, many information processing tasks can be automated with the use of ordinary, simple and inexpensive software. In most cases, all that an information professional would need is a good word processor and a piece of decent database management software. In addition, if the amount of data to be handled is large, then a powerful computer would help to speed things up. This paper describes how this was achieved in one setting: the Archives Museum of the Yapi Kredi Bank in Turkey. © 2000, MCB UP Limited
Keywords: Archives; Banking; Database management; Museums; Turkey